Clean Energy-Based Social Innovation for Sustainable Management of the Pulau Ketam Forest Reserve: A Collaborative Synergy between UNPAB and PTSS Malaysia - Sri Rahayu; Elfitra Desy Surya; Rosasmanizan Binti Ahmad; Faisal (International Journal of Management, Economic and Accounting, 2025)
This community engagement program introduces a clean energy-based social innovation approach to support the sustainable management of the Pulau Ketam Forest Reserve through a collaborative synergy between Universitas Pembangunan Panca Budi (UNPAB) and Politeknik Tuanku Syed Sirajuddin (PTSS) Malaysia. The initiative seeks to address two interconnected challenges faced by the local community: the need for reliable access to renewable energy solutions and the urgent requirement to conserve mangrove ecosystems that are vital to biodiversity, coastal protection, and community livelihoods. The program applies participatory methods, including stakeholder mapping, workshops, and training modules on renewable energy technologies tailored for community use, such as solar-powered systems for household needs, fisheries, and ecotourism facilities. These educational activities are combined with conservation practices, including mangrove rehabilitation, monitoring, and community-based stewardship. Preliminary findings indicate that integrating clean energy literacy with conservation awareness has strengthened local capacities, enhanced youth involvement, and fostered small-scale entrepreneurship opportunities in green sectors. Moreover, the synergy between academic institutions has created a living laboratory for sustainable practices that bridge education, research, and corporate social responsibility initiatives. The value of this program lies in its holistic approach, where clean energy education is not only seen as a technical solution but also as a driver of social innovation that empowers communities to protect their natural resources while improving their socio-economic resilience. This model offers a replicable framework for cross-border collaborations aiming to achieve sustainability goals in similar island and coastal ecosystems.